Formação do leitor: desafio à prática docente e à avaliação da aprendizagem - Silva, Olívia Coelho da (2016)
For a long time, throughout the history of Brazilian education, the language teaching and learning process was based on coding and decoding methods unlinked of its social use, resulting in a weakened and limited learning of reading and writing abilities. This fact has resulted in increased rates of children repeating or who left school without consolidating the literacy process. Currently this context motivated the appearance of various public policies, which the main objective has been to guarantee children the full command of the language in its various manifestations. In the development of reading competence of children, the great challenge is not only to instrumentalize them to decipher letters and put them together into words, but to build them taste and interest in reading, which requires a very deeper teaching process. Thus, this study focused in the education of the competent reader, with the main objective to investigate how does the pedagogical work of the elementary school teachers in developing this competence in children. To do this, a field work and documental research were done. It was analyzed the evaluation tools proposed by the Municipal Education Secretary of Fortaleza - SME and those ones which are developed by the school itself, which were used to evaluate the development of children reading the 2nd year. The research involved, in all, six teachers of elementary school of a public school of Fortaleza. As data collection strategies, interview and observation were used. The qualitative data coming from field collection were analyzed making use of Content Analysis (BARDIN, 2011). The relevant aspects that summarize the findings from the document review are: (1) the instruments provided by the SME presents weaknesses for proper diagnosis of the reading comprehension of students in the 2nd year of elementary school; (2) it was observed that the simulated test analyzed, in general, presented a very similar format to the external evaluation SPAECE-Alfa, however, some technical lapses were identified in the preparation of commands and responses alternatives in items that composed the test. These aspects, therefore, harm the analysis of the situation assessed, since it is an important requirement in the development of multiple choice, the obedience in elaborating items to technical and pedagogical principles expressed in the literature about the tests that assess learning. The conclusions derived from observations and interviews, highlights that the teachers showed good practice in relation to the education of competent reader, drawing up strategies and diversified resources, seeking the integration of the axes of the Portuguese language and the development of the social function of reading, and performing the evaluation of reading at different times, not limited to the use of instruments recommended by the Secretary. It is also noteworthy that in all classrooms had the reading place used by children in times when the teacher directed activities or freely in the delight moments of reading. Although some shortcomings in teaching practices and methodologies for assessing reading were identified, in general, this study found many positive aspects related to the evaluation of learning and teaching practice of school teachers investigated, which contribute to the development of reading competence children in literacy phase.